If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -6 = 14x + 1 Reorder the terms: -6 + 2x = 14x + 1 Reorder the terms: -6 + 2x = 1 + 14x Solving -6 + 2x = 1 + 14x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-14x' to each side of the equation. -6 + 2x + -14x = 1 + 14x + -14x Combine like terms: 2x + -14x = -12x -6 + -12x = 1 + 14x + -14x Combine like terms: 14x + -14x = 0 -6 + -12x = 1 + 0 -6 + -12x = 1 Add '6' to each side of the equation. -6 + 6 + -12x = 1 + 6 Combine like terms: -6 + 6 = 0 0 + -12x = 1 + 6 -12x = 1 + 6 Combine like terms: 1 + 6 = 7 -12x = 7 Divide each side by '-12'. x = -0.5833333333 Simplifying x = -0.5833333333
| 18a-a= | | 18=10y-y | | (7X^2-X-2)-(9X^2-5X+2)+(4X^2+3X-6)= | | -4(x-3)+5(2x-6)=180 | | 5v-3v=8 | | 4.71=3.14ab | | 17x-7(3x-5)-6= | | 4u+5u=.45 | | 4[Z-(10Z+59)+5]=3(Z+6) | | 5(x-2)+2(10+x)=180 | | -4=4(y-7)-8y | | (T+2)(T^2-2T-4)= | | 14x+5-3x+9= | | c-9atc=16 | | -7x^2+56x+84=0 | | 0.25t+.10(t-4)=11.60 | | 5/8x-3/4=11/8 | | 0.6t+0.4(t-0.3)=4.99 | | 2x+0.2+0.6x+3=180 | | x=x+112 | | 3y+12+5=35 | | 3x+3+15+9x=360 | | 3x+3+15+9x=180 | | 5+2a=31 | | Y=3/11x-5 | | -13P-6(5-4P)=6(P-2)-8 | | (1-0.4-1/1)*x=34 | | 7m+2=58 | | 5(x-3)+2(3+x)=180 | | 2/3x-14=0 | | ln(9x)=ln(y) | | X^2+5x-5x-6=0 |